2017
DOI: 10.1111/bjet.12601
|View full text |Cite
|
Sign up to set email alerts
|

Moving mathematics out of the classroom: Using mobile technology to enhance spontaneous focusing on quantitative relations

Abstract: Spontaneous focusing on quantitative relations (SFOR) has been shown to be a strong predictor of rational number conceptual development in late primary school. The present study outlines an intervention program that examines the possibilities to enhance late primary school students' SFOR tendency. The intervention program harnessed mobile technology in order to allow students to explore and identify quantitative relations in their everyday environment, including situations outside of the classroom. A total of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 26 publications
1
16
0
1
Order By: Relevance
“…The first steps have been taken in this direction. McMullen, Hannula-Sormunen, Kainulainen, Kiili, and Lehtinen (2017) found that a seven-week long intervention program in which sixth-graders used mobile technology to explore quantitative relations in their everyday life was successful. However, it still needs to be further explored under which conditions educational interventions to enhance SFOR may be profitable (McMullen, 2014, Vamvakoussi et al, 2016.…”
Section: Sformentioning
confidence: 99%
See 1 more Smart Citation
“…The first steps have been taken in this direction. McMullen, Hannula-Sormunen, Kainulainen, Kiili, and Lehtinen (2017) found that a seven-week long intervention program in which sixth-graders used mobile technology to explore quantitative relations in their everyday life was successful. However, it still needs to be further explored under which conditions educational interventions to enhance SFOR may be profitable (McMullen, 2014, Vamvakoussi et al, 2016.…”
Section: Sformentioning
confidence: 99%
“…As mentioned above, and Mattinen (2006) showed that SFON tendency can be promoted by means of guided focusing activities in preschool and kindergarten settings, but these intervention studies have raised critical questions, both about the spontaneous nature of children's focus on numerosities after an intervention that is explicitly aimed at increasing children's SFON, and about the broader pedagogical question whether education should stimulate young children's tendency to attend primarily at the quantitative and mathematical dimension of their environmental world (Verschaffel et al, 2017). While some first steps in the direction of stimulating other spontaneous tendencies such as SFOR (e.g., see McMullen, Hannula-Sormunen, Kainulainen, et al, 2017)) have been taken, the same questions can arguably be asked for these other mathematical focusing tendencies.…”
Section: Promotion Of Mathematical Focusing Tendenciesmentioning
confidence: 99%
“…Mobile learning techniques brought and promoted the potential of scaffolding information in a real-world context that allows learners to interact more actively with their learning content, anywhere and anytime (Bernacki et al., 2020; Devers & Panke, 2017; Domingo & Garganté, 2016; Falloon, 2017). Studies have shown that integrating the learning environment with real-time interaction and navigation-support of the learning content can enhance learners' understanding and motivation (Clarke, 2018; Ford, 2019; Jagušt et al., 2017; McMullen et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Mobile devices' unprecedented capabilities and wide acceptance among young people can expand the boundaries of mathematics teaching and offer new ways to extend mathematical thinking beyond the classroom into the real world (McMullen, Hannula-Sormunen, Kainulainen, Kiili, & Lehtinen, 2017).…”
Section: Introductionmentioning
confidence: 99%